AKTIVITAS ANTIJAMUR SENYAWA BIOAKTIF EKSTRAK Eucheuma sp. TERHADAP Aspergillus flavus - Afitri, Patrea Nurcholis; Ma'ruf, Widodo Farid; Setyati, Wilis Ari (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Eucheuma sp. is a kind of the most seaweed in Indonesia. Eucheuma sp. has acomponent of bioactive compounds which is estimated that is has potential as an antifungal.The aim of this study are to determine the content of bioactive compounds and the potentialof Eucheuma sp. extract as antifungal toward Aspergillus flavus and to determine the effect ofdifferent concentration of the solvent toward the antifungal activity of Eucheuma sp. extract.The result showed that the extract of etil asetat produced the inhibitory zone towardAspergillus flavus, while the extract of n-hexane did not produce the extract and methanoldidn’t produce inhibitory zone. The highest inhibitory zone was found at concentration of 10mg/ml if is equal with 4 mm. The result of phytochemical screening test indicated that therewere the compounds of alkaloid, and cardiac glycoside in etil acetate extract.